Establishment of Human Leukocyte Antigen-Mismatched Immune Responses after Transplantation of Human Liver Bud in Humanized Mouse Models - Mori, Akihiro (Cells, 2021)
Humanized mouse models have contributed significantly to human immunology research. In transplant immunity, human immune cell responses to donor grafts have not been reproduced in a humanized animal model. To elicit human T-cell immune responses, we generated immune-compromised nonobese diabetic/Shi-scid, IL-2RγKO Jic (NOG) with a homozygous expression of human leukocyte antigen (HLA) class I heavy chain (NOG-HLA-A2Tg) mice. After the transplantation of HLA-A2 human hematopoietic stem cells into NOG-HLA-A2Tg, we succeeded in achieving alloimmune responses after the HLA-mismatched human-induced pluripotent stem cell (hiPSC)-derived liver-like tissue transplantation. This immune response was inhibited by administering tacrolimus. In this model, we reproduced allograft rejection after the human iPSC-derived liver-like tissue transplantation. Human tissue transplantation on the humanized mouse liver surface is a good model that can predict T-cell-mediated cellular rejection that may occur when organ transplantation is performed.